2018
DOI: 10.1111/chd.12723
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and work‐life balance among pediatric cardiologists: A single center experience

Abstract: Background: Physicians are exposed to workplace factors that may result in acute or chronic stress resulting in burnout. This may impact the productivity and result in suboptimal patient care practices. Methods:We surveyed pediatric cardiology attending physicians at our institution to assess their perception of burnout and work-life balance using the Maslach Burnout Inventory and the Areas of Work-Life Survey. Results: Forty-five out of the 50 pediatric cardiology attendings responded to the survey. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…22 Social compensation in particular helps staff to deal with stressful borderline situations, to cope with a heavy workload, 23 and it can improve patient care. 23 24 25…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de la especialidad de cardiología, se pudo evidenciar que, ante la lucha con las historias clínicas y la documentación electrónica, el horario de trabajo inflexible y la falta de límites entre el trabajo y el tiempo en casa, se puede incrementar el riesgo de sufrir agotamiento. Por esta razón, Dasgupta et al (2019) recomiendan cambios en la historia clínica electrónica, trabajar a tiempo parcial, tener más control de su propio horario y aumentar los ejercicios de formación de equipos. Concluyen discutiendo sobre otros elementos como los periodos prolongados de trabajo, la imposibilidad de seguir intereses personales y la percepción de oportunidades, no solo como resultado del mérito sino como factores que inciden en el agotamiento de los trabajadores que llevan más de 10 años en su puesto actual (Dasgupta et al, 2019).…”
Section: )unclassified
“…Por esta razón, Dasgupta et al (2019) recomiendan cambios en la historia clínica electrónica, trabajar a tiempo parcial, tener más control de su propio horario y aumentar los ejercicios de formación de equipos. Concluyen discutiendo sobre otros elementos como los periodos prolongados de trabajo, la imposibilidad de seguir intereses personales y la percepción de oportunidades, no solo como resultado del mérito sino como factores que inciden en el agotamiento de los trabajadores que llevan más de 10 años en su puesto actual (Dasgupta et al, 2019).…”
Section: )unclassified